Bridge cable fireproof material, fireproof combined layer and preparation method
By using a multi-layer fireproof material composed of ceramic fiber and other raw materials and a supporting mesh layer design, the problems of easy deformation, collapse and insufficient heat insulation performance of bridge cable fireproof materials at high temperatures are solved. This achieves efficient and stable fireproof performance and a simple preparation process, making it suitable for fire protection of bridge cables.
Patent Information
- Application Number
- CN202510971611.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-11-07
AI Technical Summary
Existing fireproof materials for bridge cables are prone to deformation and collapse at high temperatures, have insufficient thermal insulation performance, and the fireproof composite layer structure is not dense enough, affecting the stability and reliability of fireproof performance. Furthermore, the manufacturing process is complex and difficult to apply on a large scale.
Fireproof materials composed of ceramic fibers, polymer-modified diatomaceous earth, mica filler, quartz powder, bauxite, hydrophobic fumed silica and silicon carbide are used to form a multi-layer protective structure. Combined with a support mesh layer and sewing thread design, a three-layer fireproof composite layer is prepared.
It effectively prevents heat transfer at high temperatures, improves the overall thermal insulation and thermal shock resistance of fireproof materials, enhances structural stability, simplifies the manufacturing process, facilitates large-scale production, and meets environmental protection requirements.
Smart Images

Figure CN120904909A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of bridge fire prevention, and particularly relates to a bridge cable fireproof material, a fireproof combined layer and a preparation method. BACKGROUND
[0002] The main cable of a suspension bridge is a key load-bearing component of the bridge, and its fireproof performance is crucial. Once the main cable catches fire, not only will it cause huge economic losses, but also will affect people's livelihood safety.
[0003] At present, the fireproof measures for the main cable mainly focus on the application of fireproof coatings and fireproof fillers. Although the traditional fireproof fillers can play a fireproof role to some extent, there are still some problems. For example, the high-temperature resistance of some fireproof fillers is insufficient, and they are prone to deformation or collapse under high temperature, resulting in reduced fireproof effect; the heat insulation performance of some fireproof fillers is not ideal, and they cannot effectively block the heat transfer to the inside of the main cable; in addition, the thermal shock resistance of the existing fireproof fillers needs to be improved, and they are prone to cracking or falling off when the temperature changes sharply during the fire, affecting the integrity of the fireproof structure.
[0004] At the same time, the structural design of the fireproof combined layer also has deficiencies. The existing fireproof combined layer mostly adopts a simple multi-layer superposition structure, and the combination between the layers is not tight enough, and it is prone to delamination or loosening under the action of high temperature and mechanical stress, affecting the stability and reliability of the fireproof performance. Moreover, the preparation process of the existing fireproof combined layer is complex, and the production efficiency is low, which is difficult to meet the demand of large-scale engineering application.
[0005] Therefore, it is of great significance to develop a kind of bridge cable fireproof material, a fireproof combined layer and a preparation method with excellent fireproof performance, high-temperature resistance, heat insulation performance and thermal shock resistance, for improving the fireproof safety of the main cable of the suspension bridge and protecting the normal operation of the bridge and the safety of people's life and property. SUMMARY
[0006] In view of the above technical problems, the application provides a kind of bridge cable fireproof material, a fireproof combined layer and a preparation method.
[0007] To achieve the above-mentioned purpose, the application provides the following technical scheme: One of the purposes of the application is to provide a kind of bridge cable fireproof material, which comprises the following raw materials by mass fraction: ceramic fiber 5-8 parts, polymer modified diatomite 10-18 parts, mica filler 8-15 parts, quartz powder 3-7 parts, bauxite 22-40 parts, hydrophobic fumed silica 40-60 parts and silicon carbide 3-6 parts.
[0008] The thermal conductivity of ceramic fiber is extremely low, and the heat insulation performance is excellent, which can effectively prevent heat transfer, and is not easy to react chemically at high temperature, and can keep the fireproof performance for a long time. At the same time, the ceramic fiber has high tensile strength and elastic modulus, which can enhance the overall mechanical properties of the fireproof filler, make up for the mechanical performance of diatomite, and keep the structure complete at high temperature. The high melting point and high strength characteristics of ceramic fiber can support the expansion layer formed by mica filler to prevent it from collapsing due to high temperature. And its fibrous structure combined with the granular structure of quartz powder forms a multi-scale heat insulation network, further improving the heat insulation effect. The high melting point and chemical stability of bauxite enable it to maintain structural integrity at high temperature, and synergize with ceramic fiber to enhance the overall heat resistance and heat insulation performance of the fireproof filler. The porous structure of hydrophobic fumed silica can further reduce the thermal conductivity of the fireproof filler, combined with the low thermal conductivity of ceramic fiber, to form a more efficient heat insulation layer. The high strength characteristics of ceramic fiber can support the porous structure of silica to prevent it from collapsing at high temperature. Silicon carbide has high melting point and good thermal conductivity, which can quickly conduct heat at high temperature to avoid local overheating. The low thermal conductivity of ceramic fiber can be combined with the thermal conductivity of silicon carbide to form a "thermal buffer" mechanism, further improving the overall heat insulation performance of the fireproof filler. That is, ceramic fiber forms a multi-scale, multi-mechanism fireproof and heat insulation system through synergistic effect with other raw materials. Its high strength, low thermal conductivity, high temperature resistance and chemical stability can significantly enhance the overall performance of the fireproof filler, making it exhibit excellent fireproof, heat insulation and mechanical properties in fire environment.
[0009] Diatomite has a porous structure and can adsorb and store a large amount of gas such as water vapor. At high temperature, polymer modified diatomite can release the adsorbed gas to form a gaseous barrier, reduce the volume percentage of oxygen, and thus inhibit the spread of flame. In addition, polymer modified diatomite can also form a molten layer at high temperature, which can act as a barrier and insulation. Moreover, combined with ceramic fiber, it can form filling and support between fibers, improving the density and heat insulation performance of the material. At the same time, combined with mica filler, quartz powder and other components, it forms a multi-layer protective structure to enhance the fireproof effect of the material.
[0010] Mica has high temperature stability and excellent heat insulation performance, which can exist stably at high temperature for a long time and is not easy to burn. When a fire occurs, the mica layer can act as a barrier to prevent or slow down the transmission of flame and high temperature to the inside of the material, thereby protecting the material from high temperature damage. Mica filler combined with ceramic fiber, polymer modified diatomite and other components can form a multi-layer protective structure inside the material. At high temperature, the mica layer can cooperate with the molten layer formed by polymer modified diatomite to jointly play the role of heat insulation and flame blocking, and also enhance the overall structural stability of the material.
[0011] Quartz powder has a high melting point and chemical stability, and is not easy to decompose or melt at high temperatures, which can provide certain fire resistance for fireproof fillers. In addition, the addition of quartz powder can improve the density and strength of the material, and enhance the thermal shock resistance of the material. Quartz powder combined with ceramic fiber, mica filler and other ingredients can form a uniform distribution inside the material, improving the overall uniformity and stability of the material. At the same time, quartz powder can cooperate with mica filler to enhance the thermal insulation performance of the material.
[0012] Bauxite has high fire resistance and chemical stability, and can maintain certain structural stability at high temperatures, providing good fire resistance for fireproof fillers. In addition, the addition of bauxite can improve the strength and hardness of the material, and enhance the compressive performance of the material. In addition, bauxite combined with ceramic fiber, mica filler, quartz powder and other ingredients can form a uniform distribution inside the material, improving the overall uniformity and stability of the material. At the same time, bauxite can cooperate with mica filler and quartz powder to enhance the thermal insulation performance of the material.
[0013] The hydrophobic fumed silica has a nano-porous structure, a large specific surface area, and a low thermal conductivity, which can effectively prevent heat transfer and play a heat insulation role. Its hydrophobicity can prevent water from entering and avoid the destruction of the insulation layer due to water evaporation, while reducing heat conduction in a fire environment. Moreover, the hydrophobic fumed silica has good chemical stability and is not prone to react with external substances, so it can maintain its performance in a high-temperature environment. The polymer-modified diatomite itself has a porous structure and can release inert gas to dilute the concentration of flammable gas. The hydrophobic fumed silica further enhances the heat insulation performance of this porous structure, and the two work together to form a more efficient insulation layer. The mica filler expands at high temperatures to form a dense insulation layer. The nano-porous structure of the hydrophobic fumed silica fills the pores of the mica filler, further enhancing the insulation effect. The quartz powder has a high melting point and good chemical stability, and fills the porous structure of the hydrophobic fumed silica, which can enhance the density and stability of the insulation layer. The particle structure of the quartz powder combines with the fibrous structure of the hydrophobic fumed silica to form a multi-scale insulation network, further improving the insulation effect. The high melting point and chemical stability of bauxite enable it to maintain its structure integrity at high temperatures. The nano-porous structure of the hydrophobic fumed silica further enhances the insulation effect, and the two work together to improve the overall heat resistance of the fireproof filler. The hydrophobicity of the hydrophobic fumed silica can prevent the performance of bauxite from being reduced by water intrusion at high temperatures. Silicon carbide has a high melting point and good thermal conductivity, which can quickly conduct heat at high temperatures to avoid local overheating. The low thermal conductivity of the hydrophobic fumed silica combined with the thermal conductivity of silicon carbide forms a "thermal buffer" mechanism, further improving the overall insulation of the fireproof filler. That is, the hydrophobic fumed silica significantly enhances the insulation and fireproof performance of the bridge cable fireproof material through its low thermal conductivity, hydrophobicity, and nano-porous structure. Its synergistic effect with other raw materials (such as polymer-modified diatomite, mica filler, quartz powder, bauxite, and silicon carbide) further optimizes the overall performance of the fireproof filler, making it exhibit excellent insulation, fireproofing, and mechanical stability in a high-temperature environment.
[0014] The high thermal conductivity of silicon carbide enables it to quickly conduct heat, avoiding local temperature from being too high, thereby effectively protecting the main cable. Its high melting point and low thermal expansion coefficient enable it to maintain its structure integrity at high temperatures, and it will not damage the fireproof layer due to thermal expansion. Moreover, silicon carbide has high hardness (Mohs hardness 9.2), which can enhance the mechanical strength of the fireproof filler.
[0015] Further, the specific preparation steps of the polymer-modified diatomite include: (1) In an ethanol solution with a mass concentration of 90%, slowly add amino silane coupling agent while adjusting the pH to 3-4 with acetic acid. After the drop is completed, continue stirring until the solution is transparent to obtain an amino silane coupling agent solution with a mass fraction of 5%; (2) The amino silane coupling agent solution prepared above is weighed, diatomite is added, stirring at room temperature for 30-60 minutes, then filtering, the filter cake is dried at 50-60℃ for 2-4 hours, then dried at 110℃ for 3-4 hours, cooling, to obtain the amino silane coupling agent modified diatomite; (3) The amino silane coupling agent modified diatomite is mixed with the polyepoxy chloropropane-dimethylamine cationic polymer solution, then dried at 45-55℃ until constant weight, the material is taken out and crushed, to obtain the polymer modified diatomite.
[0016] Further, the specific preparation steps of the mica filler include: S1, drying the mica powder in an oven at 90-110℃ for 4-6 hours, to fully remove the adsorbed water on the surface of the mica powder; S2, adding sodium metatitanate, the dried mica powder and polyethylene glycol into an ethanol aqueous solution, fully dissolving the mica powder in the ethanol aqueous solution in a constant temperature water bath at 80-100℃ for 10-12 hours; S3, slowly adding saturated ammonium chloride solution under the state of electric agitator stirring, standing for 2 hours, then centrifuging, filtering, drying and crushing, to obtain the mica filler.
[0017] Further, the diameter of the ceramic fiber is 5-8μm, and the length is 0.1-0.4mm.
[0018] The second object of the present application is to provide a preparation method of the bridge cable fireproof material, the raw materials are weighed by mass fraction, the ceramic fiber, the polymer modified diatomite, the mica filler, the quartz micro powder, the bauxite, the hydrophobic fumed silica and the silicon carbide are mixed and dried, to obtain the bridge cable fireproof material. The third object of the present application is to provide a fireproof combined layer, which comprises, from bottom to top, an outer fireproof cloth layer, the bridge cable fireproof material and an inner fireproof cloth layer.
[0019] The fourth object of the present application is to provide a preparation method of the fireproof combined layer, which comprises the following steps: The outer fireproof cloth layer is used as the bottom layer, the bridge cable fireproof material is used as the core layer, the core layer is laid on the bottom end surface of the bottom layer, to form a first structure; Then the inner fireproof cloth layer is laid on the side of the core layer away from the bottom layer, to form a second structure; The second structure is pressed, to obtain the fireproof combined layer.
[0020] The pressing means that the bridge cable fireproof material is formed into a plate shape under the extrusion of external force, and then it is packaged and combined for use.
[0021] Further, the laying thickness of the core layer is 5-10 mm; and / or The outer fireproof cloth layer is a quartz cloth with a thickness of 1-2 mm; and / or The inner fireproof cloth layer is a high-silica cloth with a thickness of 1-2 mm.
[0022] Further, the inner side of the core layer is provided with a support mesh layer.
[0023] The beneficial effects are: Enhance the strength of the core layer: the setting of the support mesh layer can effectively enhance the strength and stability of the core layer, prevent it from deforming or damaging under external force or high temperature environment, thereby improving the compression resistance and impact resistance of the entire fireproof combined layer.
[0024] Improve the bonding force: the grid structure of the support mesh layer can be closely combined with the core layer, improving the bonding force of the core layer. In the construction process, the grid intersection points of the support mesh layer can form effective connection with the cells of the sewing line, enhancing the bonding strength between the layers of materials, making the entire fireproof outer layer wrapping structure more compact and firm, and further improving its fireproof performance and service life.
[0025] Further, the outer surface of the outer fireproof cloth layer and the inner fireproof cloth layer is processed with a sewing line, the sewing line is staggered to form a plurality of cells, and the core layer is divided and limited in the cells by the sewing line.
[0026] The beneficial effects are: Enhance the structural stability: this structure is similar to the "lattice-like" reinforcement method, which can effectively prevent the core layer from shifting or gathering during use, ensuring the stability of the fireproof combined layer, so that each part can bear force uniformly when the fireproof combined layer is subjected to external force, avoiding local damage and prolonging the service life.
[0027] Improve the uniformity of fireproof performance: by dividing and limiting the core layer in the cells through the sewing line, the distribution of the core layer is more uniform, thereby ensuring the uniformity of the fireproof performance. In the event of a fire, the entire fireproof combined layer can play a more uniform fireproof role, avoiding inconsistent fireproof effect caused by local concentration or sparseness of fireproof filler, further improving the fire safety of the main cable.
[0028] Further, it further comprises a buffer sealing combined layer, the buffer sealing combined layer comprises a rubber layer and a sealing glue layer which are sequentially compounded on the outer surface of the inner fireproof cloth layer; the sealing glue layer is wrapped around the outer surface of the main cable, so that the outer fireproof cloth layer is exposed.
[0029] The beneficial effect is that the buffer sealing combined layer includes a rubber layer and a sealing glue layer, and the sealing glue layer is wrapped around the outer surface of the main cable to expose the outer fireproof cloth layer. This design can effectively prevent air from entering and avoid the decline of the heat insulation performance of the fireproof material due to air flow, thereby improving the sealing performance of the overall structure and enhancing the durability of the fireproof effect.
[0030] The above technical solution has the following beneficial effects: Excellent fireproof performance: through the synergistic effect of ceramic fiber, polymer modified diatomite, mica filler and other ingredients, a multi-layer protective structure is formed, which can effectively prevent heat from transferring to the inside of the main cable at high temperature and reduce the flame spread speed. The ingredients such as ceramic fiber, bauxite and quartz powder have high fire resistance and chemical stability, which can keep the structure stable at high temperature and prevent the material from deforming or collapsing. The mutual cooperation of various ingredients in the fireproof filler enhances the overall structural stability of the material, so that it is not easy to crack or fall off when the temperature changes sharply, ensuring the stability of the fireproof effect.
[0031] Enhanced structural stability: the multi-layer protective structure formed inside the fireproof filler enhances the overall heat insulation performance and thermal shock resistance of the material.
[0032] Efficient preparation process: the preparation process is simple and convenient for large-scale production. In the preparation process of the fireproof filler, the addition of water and ethanol not only plays the role of solvent and dispersant, but also rapidly evaporates at high temperature to take away a large amount of heat, play a cooling role, and at the same time form a gaseous barrier to inhibit the spread of flame.
[0033] Optimized fireproof combined layer design: the three-layer structure design of the fireproof combined layer is reasonable, and the combination between the layers is tight, which enhances the overall performance of the fireproof combined layer. The preparation method of the fireproof combined layer is flexible, which meets the requirements of different engineering scenes.
[0034] Environmentally friendly: the fireproof filler does not release harmful gases or substances at high temperature, which meets the environmental protection requirements. Some raw materials are recyclable, which reduces resource waste and meets the concept of sustainable development. BRIEF DESCRIPTION OF DRAWINGS
[0035] The drawings that form a part of this application provide further understanding of the present application, and the illustrative embodiments of the present application and their descriptions are used to explain the present application, and do not constitute an improper limitation on the present application. In the drawings: Figure 1 A layered schematic diagram of the integrated main cable fireproof outer layer wrapping structure provided for application example 1 is provided; Figure 2 A layered schematic diagram of the integrated main cable fireproof outer layer wrapping structure provided for application example 1 is provided; Figure 3Structure diagram of the integrated main cable fireproof outer layer wrapping structure provided for application example 1 wrapped on the main cable (stitching thread is not shown); Figure 4 Layered structure diagram of the integrated main cable fireproof outer layer wrapping structure provided for application example 2; Figure 5 Structure diagram of the support net surface layer provided for application example 3; Figure 6 Plan view diagram of the support net surface layer provided for application example 3; Figure 7 Structure diagram of the integrated main cable fireproof outer layer wrapping structure provided for application example 3 (stitching thread is not shown); Figure 8 Structure diagram of the positioning lock provided for application example 4; Figure 9 Sectional view of the positioning lock provided for application example 4; Figure 10 Structure diagram of the integrated main cable fireproof outer layer wrapping structure provided for application example 4 wrapped on the main cable (stitching thread is not shown).
[0036] Wherein: 10 is the main cable; 20 is the fireproof combined layer; 30 is the buffer sealing combined layer; 40 is the magic tape; 50 is the metal clamp; 60 is the basalt felt layer; 200 is the outer fireproof cloth layer; 201 is the inner fireproof cloth layer; 202 is the core layer; 203 is the stitching thread; 204 is the unit cell; 205 is the support net surface layer; 2050 is the positioning lock point; 2051 is the round plate; 2052 is the connecting hole; 206 is the positioning lock; 2060 is the female base; 2061 is the male plug; 2062 is the arc plate; 2063 is the arc slot; 300 is the rubber layer; 301 is the sealing rubber layer. DETAILED DESCRIPTION
[0037] The various illustrative embodiments of the present application will now be described in detail in connection with the accompanying drawings. This description is made for the purpose of demonstrating various aspects of the present application and should not be taken as limiting the present application. It is to be understood that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the present application.
[0038] It should be understood that the terms used herein are merely for the purpose of describing particular embodiments and are not intended to limit the present application. In addition, for numerical ranges in the present application, it should be understood that each intermediate value between the upper limit and the lower limit of the range is specifically disclosed. Each smaller range within any stated range or within any stated range of intermediate values is also encompassed within the present application. The upper and lower limits of these smaller ranges can be independently included or excluded from the range.
[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as those of ordinary skill in the art to which the application relates. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, preferred methods and materials are described. All documents mentioned herein are incorporated by reference to disclose and describe in full the methods and / or materials which are described therein. In case of conflict, the content of the present specification will control.
[0040] Many modifications and variations of the present application described in the specific embodiments of the application can be made by those skilled in the art without departing from the spirit or scope of the application. Other implementations of the application will be apparent to those skilled in the art from consideration of the specification and practice of the application disclosed herein. The specification and examples given are exemplary only.
[0041] As used herein, the terms "comprises", "comprising", "includes", "including", "has", "having", and the like are open-ended terms that are intended to permit but not limit the inclusion of elements or the number of elements, as well as the possibility that one or more elements can be incorporated into the composition, method, or process, or that one or more elements can be replaced by other elements or additional elements.
[0042] The bridge cable fireproof material provided by the embodiments of the present application comprises the following raw materials in parts by mass: ceramic fiber 5-8 parts, polymer modified diatomite 10-18 parts, mica filler 8-15 parts, quartz powder 3-7 parts, bauxite 22-40 parts, hydrophobic fumed silica 40-60 parts, and silicon carbide 3-6 parts.
[0043] By way of example, in the following preferred embodiments of the present application: The bridge cable fireproof material comprises ceramic fiber in 5 parts, 6 parts, 8 parts, or any range or sub-range between the aforementioned ratios; The bridge cable fireproof material comprises polymer modified diatomite in 11 parts, 15 parts, 18 parts, or any range or sub-range between the aforementioned ratios; The bridge cable fireproof material comprises mica filler in 8 parts, 10 parts, 15 parts, or any range or sub-range between the aforementioned ratios; The bridge cable fireproof material comprises quartz powder in 4 parts, 5 parts, 7 parts, or any range or sub-range between the aforementioned ratios; The bridge cable fireproof material comprises bauxite in 25 parts, 30 parts, 40 parts, or any range or sub-range between the aforementioned ratios; The bridge cable fireproof material comprises hydrophobic fumed silica in 40 parts, 50 parts, 60 parts, or any range or sub-range between the aforementioned ratios; The bridge cable fireproof material comprises silicon carbide in 3 parts, 5 parts, 6 parts, or any range or sub-range between the aforementioned ratios.
[0044] In some possible embodiments, the specific preparation steps of the polymer modified diatomite include: (1) in the ethanol solution with a mass concentration of 90%, slowly drop the amino silane coupling agent, adjust the pH to 3-4 with acetic acid, continue to stir until the solution is transparent after dropping, and obtain the amino silane coupling agent solution with a mass fraction of 5%; (2) weigh the amino silane coupling agent solution prepared above, add diatomite, stir at room temperature for 30-60 minutes, filter, dry the filter cake at 50-60 DEG C for 2-4 hours, and then dry the reaction at 110 DEG C for 3-4 hours, and obtain the amino silane coupling agent modified diatomite after cooling; (3) mix the amino silane coupling agent modified diatomite with the polyepoxy chloropropane-dimethylamine cationic polymer solution uniformly, dry at 45-55 DEG C until the weight is constant, take out the material, crush, and obtain the polymer modified diatomite.
[0045] In some possible embodiments, the specific preparation steps of the mica filler include: S1, dry the mica powder in an oven at 90-110 DEG C for 4-6 hours to sufficiently remove the adsorbed water on the surface of the mica powder; S2, add sodium metatitanate, the dried mica powder and polyethylene glycol into the ethanol aqueous solution, and fully dissolve the mica powder in the constant-temperature water bath pot at a temperature of 80-100 DEG C for 10-12 hours; S3, slowly drop the saturated ammonium chloride solution under the state of stirring by the electric mixer, stand for 2 hours, and then obtain the mica filler through centrifugation, filtration, drying and crushing.
[0046] In some possible embodiments, the diameter of the ceramic fiber is 5-8 microns, and the length is 0.1-0.4 mm.
[0047] The embodiment of the present application also provides a preparation method of the bridge cable fireproof material. According to the mass fraction, the raw materials are weighed, the ceramic fiber, the polymer modified diatomite, the mica filler, the quartz powder, the bauxite, the hydrophobic fumed silica and the silicon carbide are mixed and dried to obtain the bridge cable fireproof material.
[0048] The embodiment of the present application also provides a fireproof combined layer, which comprises, from bottom to top, an outer fireproof cloth layer 200, a bridge cable fireproof material and an inner fireproof cloth layer 201.
[0049] The embodiment of the present application also provides a preparation method of the fireproof combined layer, which comprises the following steps: The outer fireproof cloth layer 200 is used as a bottom layer, the bridge cable fireproof material is used as a core layer 202, the core layer 202 is laid on the bottom end surface of the bottom layer, and a first structure is formed. Then the inner fireproof cloth layer 201 is laid on the side of the core layer 202 away from the bottom layer, forming a second structure; The second structure is pressed to obtain the fireproof combined layer 20.
[0050] In some possible embodiments, the laying thickness of the core layer 202 is 5-10mm; and / or The outer fireproof cloth layer 200 is quartz cloth, and the thickness is 1-2mm; and / or The inner fireproof cloth layer 201 is high-silica cloth, and the thickness is 1-2mm.
[0051] In some possible embodiments, the inner side of the core layer 202 is provided with a supporting mesh layer 205.
[0052] In some possible embodiments, the outer surfaces of the outer fireproof cloth layer 200 and the inner fireproof cloth layer 201 are processed with sewing lines 203, the sewing lines 203 are staggered to form a plurality of unit cells 204, and the core layer 202 is divided and limited in the unit cells 204 by the sewing lines 203.
[0053] In some possible embodiments, the application further comprises a buffer sealing combined layer, the buffer sealing combined layer comprises a rubber layer 300 and a sealing glue layer 301 which are sequentially compounded on the outer surface of the inner fireproof cloth layer 201; the sealing glue layer 301 is wrapped around the outer surface of the main cable, so that the outer fireproof cloth layer 200 is exposed.
[0054] In the application, “parts” are all measured by “mass parts” unless otherwise specified.
[0055] In the application, “room temperature” is measured at “25±2℃” unless otherwise specified.
[0056] The raw materials used in the application are all purchased from the market. The ceramic fiber is purchased from Jiangsu Yisenmei New Material Technology Co., Ltd.; the diatomite is purchased from Jiangsu Lvpin Diatom Mud Technology Co., Ltd.; the mica powder is purchased from Jiangyin Youjia Pearl Mica Co., Ltd.; the quartz micro powder is purchased from Lianyungang Changtong Silicon Micro Powder Co., Ltd.; the bauxite is purchased from Wuxi Bishui Blue Environmental Protection Technology Co., Ltd.; the hydrophobic fumed silica is purchased from Jiangsu Cangguang Duwa Chemical Industry (Shanghai) Co., Ltd.; and the silicon carbide is purchased from Jiangsu Huaneng Silicon Carbon Ceramic Co., Ltd.
[0057] The application has the following advantages. 1)Excellent fireproof performance: Through the synergistic effect of ceramic fiber, polymer modified diatomite, mica filler and other components, a multi-layer protective structure is formed, which can effectively prevent heat from transferring to the main cable interior at high temperatures, reducing the flame spread speed. Ceramic fiber, bauxite, quartz powder and other components have high fire resistance and chemical stability, which can maintain structural stability at high temperatures, preventing material deformation or collapse. The combination of various components in the fireproof filler enhances the overall structural stability of the material, making it less likely to crack or fall off when the temperature changes rapidly, ensuring the stability of the fireproof effect.
[0058] 2)Enhanced structural stability: The fireproof filler forms a multi-layer protective structure, and the molten layer and heat insulation layer formed by polymer modified diatomite and mica filler at high temperatures cooperate with each other, enhancing the overall thermal insulation performance and thermal shock resistance of the material. Ceramic fiber as the base material provides a high-strength and tough support skeleton, preventing excessive deformation or collapse of the material when heated, while combining with other inorganic components to improve the density and stability of the material.
[0059] 3)High-efficiency preparation process: The raw materials used are common industrial materials, the preparation process is simple and easy to operate, and it is easy to mass-produce. During the preparation of the fireproof filler, the addition of water and ethanol not only plays the role of solvent and dispersant, but also rapidly evaporates at high temperatures, taking away a large amount of heat and playing a cooling role, while forming a gaseous barrier to inhibit flame spread.
[0060] 4)Optimized fireproof combination layer 20 design: The fireproof combination layer 20 is composed of bridge cable fireproof material, outer fireproof cloth layer 200 and inner fireproof cloth layer 201, the three-layer structure design is reasonable, and the combination between layers is tight, enhancing the overall performance of the fireproof combination layer. The preparation method of the fireproof combination layer 20 is flexible, and the thickness of the core layer 202, the cloth layer material and the setting of the buffer sealing combination layer can be adjusted according to actual needs to meet the requirements of different engineering scenes. The outer surface of the outer fireproof cloth layer 200 and the inner fireproof cloth layer 201 is processed with sewing thread 203, which forms multiple unit cells 204 in staggered manner, limiting the core layer 202 within the unit cells 204, further enhancing the structural stability and fireproof performance of the fireproof combination layer 20.
[0061] 5)Environmentally friendly: The fireproof filler does not release harmful gases or substances at high temperatures, meeting environmental protection requirements. Some raw materials (such as ceramic fiber, bauxite, etc.) are recyclable, reducing resource waste and meeting the concept of sustainable development.
[0062] The technical solutions of the present application are further illustrated by the following examples. Example
[0063] A bridge cable fireproof material, comprising the following raw materials by mass fraction: ceramic fiber 6 parts, polymer modified diatomite 15 parts, mica filler 10 parts, quartz powder 5 parts, bauxite 30 parts, hydrophobic fumed silica 50 parts and silicon carbide 5 parts.
[0064] A preparation method of a bridge cable fireproof material: Preparation of polymer modified diatomite: (1) In an ethanol solution with a mass concentration of 90%, slowly add amino silane coupling agent while adjusting the pH to 4 with acetic acid. After the drop is complete, continue stirring until the solution is transparent to obtain an amino silane coupling agent solution with a mass fraction of 5%; (2) Weigh the amino silane coupling agent solution prepared above, add 3g of diatomite, stir at room temperature for 50 minutes, then filter, dry the filter cake at 55℃ for 3 hours, then dry at 110℃ for 3.5 hours, and then cool to room temperature to obtain amino silane coupling agent modified diatomite; (3) Mix the amino silane coupling agent modified diatomite with 8mL of polyepoxy chloropropane-dimethylamine cationic polymer solution uniformly, then dry at 50℃ until the weight is constant, take out the material, crush, and obtain polymer modified diatomite; Preparation of mica filler: S1, dry the mica powder in an oven at 100℃ for 5 hours to fully remove the adsorbed water on the surface of the mica powder; S2, add 0.4g of sodium metatitanate, 1.2g of dried mica powder and 2mL of polyethylene glycol to 10mL of ethanol solution, and fully dissolve the mica powder in a constant temperature water bath at 90℃ for 11 hours; S3, slowly add 0.2mL of saturated ammonium chloride solution under the stirring of an electric mixer, stand for 2 hours, then centrifuge, filter, dry and crush to obtain the mica filler; (Three) Weigh the raw materials by mass fraction, mix the ceramic fiber, polymer modified diatomite, mica filler, quartz powder, bauxite, hydrophobic fumed silica and silicon carbide uniformly, dry, and press to form a bridge cable fireproof material.
[0065] Preparation of a fireproof combined layer 20: Take the fireproof combined layer 20 (quartz cloth) with a thickness of 1.5mm as the bottom layer, take the bridge cable fireproof material as the core layer 202, lay the core layer 202 on the bottom layer with a thickness of 7mm, then lay the inner fireproof cloth layer 201 (high-silicon cloth) with a thickness of 1.5mm on the surface, press to obtain the fireproof combined layer 20. Example 2
[0066] The same as example 1, except that ceramic fiber 8 parts, polymer modified diatomite 18 parts, mica filler 8 parts, quartz powder 7 parts, bauxite 25 parts, hydrophobic fumed silica 40 parts and silicon carbide 6 parts. Example 3
[0067] The same as example 1, except that ceramic fiber 5 parts, polymer modified diatomite 11 parts, mica filler 15 parts, quartz powder 4 parts, bauxite 40 parts, hydrophobic fumed silica 60 parts and silicon carbide 3 parts.
[0068] Comparative example 1 The same as example 1, except that the polymer modified diatomite is replaced by diatomite of the same mass.
[0069] Comparative example 2 The same as example 1, except that the bauxite is replaced by quartz powder of the same mass.
[0070] Comparative example 3 The same as example 1, except that 15 parts of magnesium aluminate spinel are added.
[0071] Fireproof performance test: The fireproof time of the fireproof combination layer 20 prepared by examples 1-3 and comparative examples 1-3 is tested by using an electric furnace, the fireproof performance is expressed by the fireproof time, and the longer the fireproof time is, the better the fireproof performance is. The time when the surface temperature of the steel wire breaks through 300℃ under the environment of 1000℃ is recorded as the fireproof time. The results are shown in Table 1.
[0072] Table 1 fireproof time (min) of the fireproof combination layer of examples 1-3 and comparative examples 1-3 ; As can be seen from Table 1, the fireproof combination layer 20 prepared by examples 1-3 can ensure that the time when the surface temperature of the steel wire breaks through 300℃ under the high temperature environment of about 1000℃ is greater than 136 minutes, while the fireproof time of comparative example 1 is obviously shortened after replacing the raw material type; the fireproof time of comparative example 2 is also obviously shortened under the condition that the total amount of raw materials is not changed, which shows that there is an interaction relationship between the raw materials in the application; the performance of comparative example 3 is not obviously improved after adding a new fireproof raw material, which shows that the effect of the application is not the superposition of the performance of a single raw material.
[0073] Application example 1 Referring to the accompanying drawings, Figure 1 , the application example is the application of the structure formed by example 1, which is used for wrapping outside the main cable 10 of a suspension bridge; comprising: a fireproof combination layer 20 and a buffer sealing combination layer 30: The fireproof combination layer 20 comprises an outer fireproof cloth layer 200, an inner fireproof cloth layer 201 and a core layer 202, the outer fireproof cloth layer 200 and the inner fireproof cloth layer 201 wrap the core layer 202 inside, and the core layer 202 is a flexible layered structure formed by mixing various fireproof powders by adhesion. The buffer sealing combination layer 30 comprises a rubber layer 300 and a sealing glue layer 301 which are sequentially compounded on the outer surface of the inner fireproof cloth layer 201; the sealing glue layer 301 is attached to the outer surface of the main cable 10 to wrap the outer fireproof cloth layer 200.
[0074] Referring to the accompanying drawings Figure 2 The outer surface of the outer fireproof cloth layer 200 and the inner fireproof cloth layer 201 is processed with sewing threads 203, the sewing threads 203 are staggered to form a plurality of unit cells 204, and the core layer 202 is divided and limited in the unit cells 204 by the sewing threads 203.
[0075] Further, the outer fireproof cloth layer 200 and the inner fireproof cloth layer 201 are any one of quartz cloth and high-silica cloth; The rubber layer 300 is made of silicone rubber material; The sealing glue layer 301 is butyl glue.
[0076] In the application example, the outer fireproof cloth layer 200 is quartz cloth, which can meet the fireproof requirement of 1200℃, and the inner fireproof cloth layer 201 is high-silica cloth, which can meet the fireproof requirement of 1050℃.
[0077] Further, in order to meet the rapid positioning, one side edge of the outer surface of the outer fireproof cloth layer 200 and the other side edge of the inner surface of the sealing glue layer 301 are provided with magic tapes 40 which can be enclosed and buckled, and after winding, rapid pre-tightening force positioning can be realized.
[0078] Referring to the accompanying drawings Figure 3 After the overall structure composed of the fireproof combination layer 20 and the buffer sealing combination layer 30 is wrapped outside the main cable 10, the metal hoop 50 is tightened outside the outer fireproof cloth layer 200.
[0079] In the application example, the traditional fastening mode of tightening the metal hoop 50 is still adopted to realize the fixation, but since the integrated main cable fireproof outer layer wrapping structure provided in the application example has the rubber layer 300, the tightening action of the metal hoop 50 can be alleviated by the rubber layer 300, so as to prevent the hard compression of the main cable 10, which causes damage to the core layer 202.
[0080] In order to further improve the protection effect, after the metal hoop 50 is connected, basalt felt layer 60 is bonded and laid on the arc-shaped top surface of the overall structure. The purpose of setting the basalt felt layer 60 in the application example is to facilitate the walking of the staff in the later maintenance process, and the basalt felt layer 60 can play a protective role to prevent damage to the core layer 202 caused by direct treading.
[0081] Meanwhile, in order to ensure the compatibility between the basalt felt layer 60 and the integrated fireproof outer layer of the main cable, the bonding joints of the overall structure correspond to the basalt felt layer 60, thereby improving the strength of the bonding joints of the overall structure through the bonding of the basalt felt layer 60.
[0082] Application Example 2: This application example is a further improvement on Application Example 1. To enhance the strength and adhesion of the core layer 202, as follows: Figure 4 As shown, a support mesh layer 205 is provided on the inner side of the core layer 202. The support mesh layer 205 has an interlaced mesh structure, which is embedded inside the core layer 202 during the pressing process.
[0083] like Figure 4 As shown, the sewing thread 203 forms multiple cells 204, and the support mesh layer 205 also forms multiple grids. During the processing, the intersection of the grids of the support mesh layer 205 falls into the cells 204 of the sewing thread 203, which is equivalent to connecting the diagonals of the cells 204. This will not affect the sewing process of the sewing thread 203, and at the same time, it is also beneficial to improve the adhesion.
[0084] In this application example, the support mesh layer 205 is made of basalt.
[0085] Application Example 3: This application example is a further improvement on application example 2. In order to improve the structural stability of the support mesh layer 205 and the strength of the overall structure, positioning locking points 2050 are evenly distributed on the support mesh layer 205. Positioning locking points 2050 are connected to positioning buckles 206. Positioning buckles 206 penetrate the outer fireproof cloth layer 200, the inner fireproof cloth layer 201 and the core layer 202.
[0086] See appendix Figure 5 and attached Figure 6 The positioning locking point 2050 is selected at the intersection of the grid of the supporting mesh layer 205. A circular piece 2051 is made at the intersection. A connecting hole 2052 is opened on the circular piece 2051, and the positioning lock 206 can pass through the connecting hole 2052 for connection.
[0087] After being connected by the positioning latches 206, the supporting mesh layer 205, the outer fireproof cloth layer 200, and the inner fireproof cloth layer 201 are mechanically combined to form a whole. The outer fireproof cloth layer 200 and the inner fireproof cloth layer 201 lock the position of the supporting mesh layer 205, and the sewing thread 203 also effectively limits the position of the supporting mesh layer 205. At the same time, the supporting mesh layer 205 improves the adhesion of the core layer 202, making the overall structure more integrated.
[0088] The integrated main cable fireproof outer layer wrapping structure after connecting the positioning lock buckle 206 is as shown in Figure 7 .
[0089] Application Example 4: Referring to the accompanying Figure 8 and the accompanying Figure 9 , the application example discloses the specific structure of the positioning lock buckle 206 provided in the application example 3, the positioning lock buckle 206 comprises: a female head base 2060 and a male head plug 2061, the female head base 2060 has an arc-shaped plate 2062 matched with the arc-shaped surface of the main cable 10, the female head on the arc-shaped plate 2062 corresponds to the connecting hole 2052 on the disc 2051, the male head plug 2061 is inserted into the female head on the arc-shaped plate 2062 through the connecting hole 2052, when assembled, the whole surface layer can be directly broken at the position corresponding to the connecting hole 2052 on the disc 2051, and the connecting hole 2052 is sealed by coating glue after connection.
[0090] Further, the exposed head of the male head plug 2061 has an arc-shaped groove 2063, in this way, the metal hoop 50 can be tightened in the arc-shaped groove 2063 of the male head plug 2061, which plays a tightening role while preventing the metal hoop 50 from directly contacting the integrated main cable fireproof outer layer wrapping structure, preventing the core layer 202 from being compressed and damaged, and the structure after connection is as shown in Figure 10 .
[0091] Therefore, in order to meet the cooperation of the metal hoop 50 and the arc-shaped groove 2063, the arrangement form of the positioning lock buckle 206 is as shown in Figure 7 , after being enclosed, three annular rings are formed, each annular ring has four evenly distributed positioning lock buckles 206, which can be directly used as the support of the metal hoop 50.
[0092] The above is only the preferred specific implementation of the present application, but the protection scope of the present application is not limited to this, any person skilled in the art can easily think of changes or replacements within the technical range disclosed by the present application, which should be covered in the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. A fireproofing material for bridge cables, characterized by, The raw materials include the following components by mass: ceramic fiber 5-8 parts, polymer modified diatomite 10-18 parts, mica filler 8-15 parts, quartz powder 3-7 parts, bauxite 22-40 parts, hydrophobic fumed silica 40-60 parts, and silicon carbide 3-6 parts.
2. A method of preparing a fireproofing material for bridge cables as claimed in claim 1, characterized in that, The method comprises the following steps: The raw materials are weighed by mass fraction, and the ceramic fiber, polymer modified diatomite, mica filler, quartz powder, bauxite, hydrophobic fumed silica, and silicon carbide are mixed, dried, and obtained as the bridge cable fireproof material.
3. The method of claim 2, wherein the bridge cable fireproofing material is prepared by the steps of: The specific preparation steps of the polymer modified diatomite include: In the ethanol solution, the amino silane coupling agent is added dropwise, the pH is adjusted to be acidic with acetic acid, and after the dropwise addition is completed, the solution is continuously stirred until it is transparent, to obtain an amino silane coupling agent solution; The diatomite is added to the amino silane coupling agent solution, stirred, filtered, and dried, to obtain amino silane coupling agent modified diatomite; The amino silane coupling agent modified diatomite is mixed with a polyepoxy chloropropane-dimethylamine cationic polymer solution, and then dried to constant weight, to obtain polymer modified diatomite.
4. The method of claim 2 or 3, wherein the bridge cable fireproofing material is prepared by the steps of: The specific preparation steps of the mica filler include: Sodium metatitanate, dried mica powder, and polyethylene glycol are added to an ethanol aqueous solution, and heated to react until the mica powder is dissolved; A saturated ammonium chloride solution is slowly added dropwise under stirring, and after standing, the mica filler is obtained by centrifugation, filtration, drying, and crushing.
5. A fireproofing assembly comprising the bridge cable fireproofing material of claim 1, wherein, It also includes an outer fireproof cloth layer and an inner fireproof cloth layer.
6. The fire protective composite layer of claim 5, wherein, It also includes a buffer sealing combined layer, which includes a rubber layer and a sealing adhesive layer that are sequentially compounded on the outer surface of the inner fireproof cloth layer, and the sealing adhesive layer is wrapped around the outer surface of the main cable, so that the outer fireproof cloth layer is exposed.
7. A method of preparing a fire barrier assembly as defined in claim 5, wherein, The method comprises the following steps: The outer fireproof cloth layer is used as the bottom layer, and the bridge cable fireproof material is used as the core layer, which is laid on the bottom end surface of the bottom layer to form a first structure; Then the inner fireproof cloth layer is laid on the side of the core layer away from the bottom layer to form a second structure; The second structure is pressed to obtain a fireproof combined layer.
8. The preparation method of the fireproof combined layer according to claim 7, wherein: The laying thickness of the core layer is 5-10 mm; The outer fireproof cloth layer is quartz cloth with a thickness of 1-2 mm; The inner fireproof cloth layer is high-silicon cloth with a thickness of 1-2 mm.
9. The method of claim 8, wherein the fire barrier assembly is prepared by, The inner side of the core layer is provided with a support mesh layer.
10. The method of claim 9, wherein the fire barrier assembly is prepared by, The outer surfaces of the outer fireproof cloth layer and the inner fireproof cloth layer are processed with sewing threads, the sewing threads are staggered to form a plurality of unit cells, and the core layer is divided and limited in the unit cells by the sewing threads.